Who Undermines the Peace at the Ballot Box? The Case of Colombia - Pechenkina, Anna O. (Terrorism and political violence, 2022)
Electoral politics and violent civil conflict often coexist. Citizens exposed and unexposed to violence bear the costs of conflict unevenly and, thus, conceive of militant vs. accommodationist state response to the perpetrators of violence differently. The literature has found that victims of political violence tend to endorse militant state response against nonstate actors seen as responsible. This result is mostly based on secessionist conflicts in which victims of violence are often shielded from the costs of state counterinsurgency or counterterrorism campaigns. By contrast, we argue, in non-secessionist conflicts, individuals exposed to violence tend to also experience the state militant anti-guerrilla operations, which often lead to state abuses of civilians. We expect that civilians exposed to nonstate and state attacks will be more likely to support pro-peace policies. We find support for this argument analyzing Colombia’s 2014 presidential election and 2016 peace agreement referendum. In addition, we use original data on local candidates’ pro- and anti-peace process positions in Colombia’s 2014 congressional election to test the underlying logic of the argument that local communities exposed to both nonstate and state violence are more likely to demand pro-peace policies.